Pengaruh Beberapa Jenis Talas (Xanthosoma sp) dan Bahan Fortifikasi Pangan dalam Pembuatan Mie - Hermianti, Wilsa; Silfia, Silfia (Jurnal Litbang Industri, 2011)
Noodle is a food product processed from wheat flour is very popular among many people because it is easy and fast in the serving as well as glut so it is often used as a food substitute for rice. To anticipate and reduce dependence on wheat, the making of noodles can be replaced with crops such as taro tubers. Taro plant is one of the major crops among the various types of tubers in the tropics as a source of carbohydrate.There are 60 local varieties of taro reported in West Sumatra, but only three types of taro are easily found in the market. They are purple stems Colocasia esculenta, green stems Colocasia esculenta and kimpul taro (Xanthosoma sagittifolium). Research was carried out by combination of treatment type of taro and fortification materials (red sweet potatoes, carrots, and spinach) to enrich the nutrional and to vary the appearance of noodles. Organoleptic tests of the noodle produced including color, aroma, flavor, texture, and analysis of water content, ash content, protein, crude fiber, carbohydrates and fats as well as observations of the shelf life of the products based on water content and visual appearance for 3 months of storage. Research results indicate that the optimal results was the treatment of taro noodle from kimpul taro substitute with 50% flour and 7% additional material of spinach (T2P3). The taro noodles product had moisture content of 7.40%, 64.54% of carbohydrate, crude fiber of 2.71%, protein content of 11.81%, 11.19% of fat, calorific value of 405.5 calorie and organoleptic tests were preferred by panelists.ABSTRAKMie merupakan produk pangan hasil olahan tepung terigu yang sangat disukai berbagai kalangan masyarakat karena mudah dan cepat dalam penyajian serta mengenyangkan sehingga sering dijadikan sebagai makanan pengganti nasi. Untuk mengantisipasi dan mengurangi ketergantungan terhadap terigu dalam pembuatan mie dapat disubsitusi dengan tanaman umbi-umbian seperti talas. Tanaman talas adalah salah satu jenis tanaman utama diantara bermacam umbi-umbian di daerah tropis sebagai sumber karbohidrat. Tanaman talas juga banyak jenisnya, di Sumatera Barat dilaporkan ada 60 varietas lokal talas namun yang banyak ditemui di pasaran adalah dari jenis Colocasia esculenta batang ungu dan batang hijau serta kimpul (Xanthosoma sagittifolium). Penelitian dilakukan dengan perlakuan jenis talas dan bahan fortifikasi untuk memperkaya gizi dan variasi penampilan mie yakni penggunaan ubi jalar merah, wortel, dan bayam. Uji organoleptik terhadap mie yang dihasilkan meliputi warna, aroma, rasa dan tekstur dan analisis kadar air, kadar abu, protein, serat kasar, karbohidrat dan lemak serta pengamatan daya simpan yakni kadar air dan penampakan secara visual selama 3 bulan penyimpanan. Hasil penelitan menunjukkan bahwa perlakuan yang memberikan hasil optimal adalah pada perlakuan pembuatan mie dari talas kimpul dengan subsitusi terigu 50% dan bahan tambahan bayam 7% (T2P3) dengan kadar air produk mie talas 7,40%, karbohidrat 64,54%, serat kasar 2,71%, kadar protein 11,81%, lemak 11,19%, nilai kalori 405,5 kalori dan uji organoleptik disukai oleh panelis.